2022
DOI: 10.1111/ctr.14704
|View full text |Cite
|
Sign up to set email alerts
|

Are short‐term complications associated with poor allograft and patient survival after liver transplantation? A systematic review of the literature and expert panel recommendations

Abstract: Background: Maximizing patient and allograft survival after liver transplant (LT) is important from both a patient care and organ utilization perspective. Although individual studies have addressed the effects of short-term post-LT complications on a limited scale, there has not been a systematic review of the literature formally assessing the potential effects of early complications on long-term outcomes.Objectives: To identify whether short-term complications after LT affect allograft and overall survival, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
3
0
2
Order By: Relevance
“…1,81 Rather, the incidence of complications, quality of recovery, and quality of life should be the targets to improve in perioperative studies conducted in this population. [82][83][84] Despite the limited QoE on important postoperative outcomes, we observed that more potent vasoconstrictors might help reduce intraoperative bleeding, the best QoE we found being on the blood loss reduction effect of terlipressin (moderate QoE). Terlipressin is a potent vasoconstrictor with a specific splanchnic effect, whereas phenylephrine is a potent alpha-1 agonist known to increase venous return to the central circulation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…1,81 Rather, the incidence of complications, quality of recovery, and quality of life should be the targets to improve in perioperative studies conducted in this population. [82][83][84] Despite the limited QoE on important postoperative outcomes, we observed that more potent vasoconstrictors might help reduce intraoperative bleeding, the best QoE we found being on the blood loss reduction effect of terlipressin (moderate QoE). Terlipressin is a potent vasoconstrictor with a specific splanchnic effect, whereas phenylephrine is a potent alpha-1 agonist known to increase venous return to the central circulation.…”
Section: Discussionmentioning
confidence: 74%
“…1,81 Rather, the incidence of complications, quality of recovery, and quality of life should be the targets to improve in perioperative studies conducted in this population. 82-84…”
Section: Discussionmentioning
confidence: 99%
“…В свою очередь, максимальное увеличение выживаемости пациента и аллотрансплантата после ОТП важно с точки зрения как самого лечения, так и рационального и максимально эффективного использования органов [7].…”
Section: Discussionunclassified
“…Однако среди факторов, наиболее значимо влияющих на показатели выживаемости, многие авторы обозначают развитие бактериальных инфекций, тяжелое ишемически-реперфузионное поражение, острое отторжение трансплантата печени, возникающие в раннем посттрансплантационном периоде [5,[7][8][9][10]. В то же время исследований, рассматривающих влияние осложнений раннего посттрансплантационного периода на результаты отдаленной выживаемости и прицельно оценивающих потенциальное влияние ранних осложнений на отдаленные результаты, попрежнему недостаточно [7].…”
Section: Discussionunclassified
“…Liver transplantation (LT) is an established life-saving treatment for end-stage liver diseases and early hepatocellular carcinoma (HCC) [ 1 5 ]. During LT, the liver is subjected to ischemia and reperfusion injury (IRI), leading to early allograft dysfunction (EAD) and even primary graft nonfunction (PNF), compromising the survival of grafts and recipients, especially for extended criteria donors [ 6 8 ]. Despite great clinical significance, there is no effective treatment for liver IRI yet, and about 25% of LT recipients still develop EAD.…”
Section: Introductionmentioning
confidence: 99%